Penggunaan Software Sketchup dan BIM dalam Proses Perancangan Bangunan Bentang Lebar Studi Kasus : Masjid Agung Medan - Dara Wisdianti; Tema Syukur Lase; Fazar Aulia (Jurnal Teknik dan Teknologi Indonesia, 2024)
Building Information Modeling (BIM) is a process that involves creating and managing digital information about the physical and functional characteristics of a building. This research aims to find out the process of the stages of using Sketchup and BIM software in the process of designing wide-span buildings. in the Wide-Span Building Design Process in this case the object of research focuses on the Medan Great Mosque. This research method uses descriptive qualitative in which this research describes the process stages of using Sketchup and BIM software. The results of this study explain that the use of BIM (Building Information Modeling) and Sketchup Software greatly support and facilitate the design and construction process in building design support and facilitate the design and construction process in the design of the Medan Great Mosque building.